Effectiveness of a Spousal Support Program in Improving the Quality of Life of Male Patients Undergoing Infertility Treatment: A Pilot Study - Kyoko Asazawa; Mina Jitsuzaki; Akiko Mori; Tomohiko Ichikawa; Katsuko Shinozaki (Shiraz University of Medical Sciences, 2020)
Background: There are various causes of male infertility. Infertile men usually have a low quality of life (QoL) and a high level of stress compared with men without infertility problems. The present study aimed to examine the effects of a spousal support program to enhance the QoL of male patients undergoing infertility treatment. Methods: The present non-randomized controlled trial was conducted among 38 infertile couples in Tokyo (Japan) during April-August 2018. The study employed a quasi-experimental design (pretest-posttest with comparison) using purposive sampling. The levels of QoL, distress, and spousal support were measured using self-administered valid and reliable questionnaires. The paired t test was used to analyze pre- and post-intervention data with SPSS software (version 23.0). P Results: There were significant differences between the pre-test and post-test scores for the relational and emotional sub-scales of QoL. The paired t test results showed that the post-test emotional sub-scale (66.9±16.9) was significantly higher than the pre-test emotional sub-scale (58.5±13.5; t (30)=2.2, P=0.04). Similarly, the post-test relational sub-scale (71.2±21.6) was significantly higher than its pre-test score (60.8±13.7; t (30)=2.3, P=0.03). The majority of the participants 23 (74.2%) expressed satisfaction with the program. Conclusion: The spousal support program was well-received and significantly improved part of the QoL of men who were infertile due to various causes.